APPLICATION OF THE NORMS OF THE WORLD TRADE ORGANIZATION ACTS ON COPYRIGHT AND RELATED RIGHTS (Academicia Globe: Inderscience Research, 2022)
The article analyzes aspects of the activities of the World Trade Organization, which is an international organization, related to the protection of intellectual property, in particular, car rights and related rights, features of trade turnover of intellectual property objects, transactions in trade areas of intellectual property (TRIPS).The proposals related to the impact of this document on the development of national legislation in this area, its role in the development of new norms in the field of copyright and related rights are presented. The scientific and theoretical views of scientists on the industry and the personal views of the author are indicated.